Vitamin D3 Supplementation in the Diet on Production Performance and Physical Egg Quality of Quail (Coturnix coturnix japonica) - Widya Hermana; Rifka Syafika Aulia; Zahra Rizki Fauziyyah Gunawan; Sumiati Sumiati; Rizky Nadia (Faculty of Animal Science, Universitas Gadjah Mada, 2026)
This study aimed to evaluate the effect of dietary supplementation with vitamin D₃ on production performance and physical egg quality in quail. The experiment was conducted on 450 quails aged 22 weeks, which were reared until 27 weeks of age. A Completely Randomized Design (CRD) was applied, consisting of three treatments with five replications each: P0 = control diet without vitamin D₃ supplementation (basal diet), P1 = basal diet + 1.0 g/kg vitamin D₃ supplementation, and P2 = basal diet + 1.5 g/kg vitamin D₃ supplementation. Data were analyzed using Analysis of Variance (ANOVA), followed by Duncan’s multiple range test when significant differences were detected. The results showed that the supplementation of 1.5 g/kg vitamin D₃ contibuted to higher egg production, which was refleted by significant (P<0.05) improvements quail day production (QDP), egg mass, and feed conversion ratio (FCR), and very significant (P<0.01) enhancement yolk color. Supplementation of 1.0 g/kg and 1.5 g/kg Vitamin D₃ did not affect egg index, yolk percentage, albumen percentage, shell percentage, shell thickness, and Haugh unit. In conclusion, dietary supplementation of vitamin D₃ at the optimal level of 1.5 g/kg effectively enhanced quail production performance and yolk color, without negatively impacting egg physical quality